Early warning system of government debt crises - Christian Dreger; Konstantin A. Kholodilin (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
The European debt crisis has revealed serious deficiencies and risks on a proper functioning of the monetary union. Against this backdrop, early warning systems are of crucial importance. In this study that focuses on euro area member states, the robustness of early warning systems to predict crises of government debt is evaluated. Robustness is captured via several dimensions, such as the chronology of past crises, econometric methods, and the selection of indicators in forecast combinations. The chosen approach is shown to be crucial for the results. Therefore, the construction of early warning systems should be based on a wide set of variables and methods in order to be able to draw reliable conclusions.
Keywords: C23; C25; H63; 330; sovereign debt crises; multiple bubbles; signal approach; logit; panel data model